Act of defiance [compact disc, unabridged] - Andrews, Brian, 1973-; Wilson, Jeffrey, 1963-; Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan novel., 2024)
US intelligence is reporting turmoil in the Russian navy. Their deadliest submarine, the Belgorod, has unexpectedly launched, and taken along with it a long list of questions. Who authorized the departure? What mission is it on? And, most disturbing of all, what weapons do the giant doors on the sub's bow hide? It's been four decades since a similar incident with the Soviet sub, Red October, ended happily, thanks to a young CIA analyst named Jack Ryan. Now, President Jack Ryan finds himself with fleets of ships, squadrons of jets, and teams of SEALs at his command, but what he doesn't have is insight into the plans of the Belgorod's commander. It falls to a younger generation of Ryans to do the dangerous work that will reveal that information. But there's always a price to be paid. When the final moments tick away, will Jack Ryan have to choose between the safety of his country and the safety of his child?